Psychotrope, dépression et intersubjectivité : l’épistémologie clinique de Roland Kuhn ou le faire science de la psychiatrie existentielle - Vincent Pidoux (Histoire, Médecine et Santé, 2015)
This article aims to question what it means to do scientific research in psychiatry, and what science has to do with the “psy” clinic. This questioning is part of a broader issue, which is the relationship between theory and practice in the field of mental health. A case study is described:the clinical and reflexive epistemology proposed by Swiss psychiatrist Roland Kuhn (1912-2005). His epistemology was determining in the evaluation of the antidepressant effects of the first tricyclic, imipramine, which the Swiss pharmaceutical compagny Geigy planned for the same antipsychotic use as chlorpromazine. I show in this article how Kuhn’s approach articulates existential and phenomenological analysis, classical nosography, and the organic etiology of depression. I show how Kuhn’s work articulates theory and practice in a reflexive way, and how he used a “constructivist” approach which emphasized the role of the molecule, of the clinical-researcher, of the patients and of the intersubjectivity which link them together.